FECUNDITY OF TWO FRESHWATER PRAWNS, MACROBRACHIUM LAMARREI LAMARREI AND M. DAYANUM - SARKAR, INDRANI; BASU, ARNAB; ROY, SHEELA; DUTTA, SIDDHARTHA (Journal of the Inland Fisheries Society of India, 2021)
The fecundity is an essential information for developing the aquaculture industry and management policies. The study of fecundity of any species is important to have a full understanding of its breeding biology. The evaluation of fecundity is necessary to measure the reproductive fitness of Crustanceans (Nazari et al., 2003) and is directly influenced by natural selection. Fecundity and breeding frequencies are directly related to a species life strategy (Oh and Hartnoll, 2004).